Two years of enhanced surveillance of sexually-transmitted chlamydia in South East Queensland - Young, Megan K; McCall, Bradley J; Jardine, David (Communicable Diseases Intelligence, 2006)
The National Sexually Transmissible Infections Strategy 2005–2008, released in 2005, lists exploring and addressing barriers to enhanced data collection for chlamydia surveillance among the actions required for chlamydia control and prevention. This study describes a method of enhanced surveillance of sexually transmitted chlamydia notifications undertaken in South East Queensland, and the epidemiology and management of chlamydia over the study period. The service providers of a random sample of chlamydia notifications meeting preset inclusion criteria were faxed an information package and questionnaire. Telephone follow-up was initiated for non-responders. The first year of data were compared to the second year of data. The overall response rate was 93.2 per cent. Males were more likely than females to be tested because of symptoms in the first year of the study, but not the second. Females were 5.2 times (95% CI 2.43, 10.91) more likely to be screened on the suggestion of the service provider than males. The positivity rate among those tested for sexually transmitted chlamydia increased across the study period. An information package and questionnaire faxed to notifying clinicians is a simple and effective means of conducting enhanced surveillance of sexually transmitted chlamydia. An increase in the screening of males may be contributing to the increasing rate of notifications. An increasing positivity rate among all those tested for chlamydia may be due to more prevalent disease, or more focused testing of high risk groups. Commun Dis Intell 2006;30:456–461.